Nitrogen Chemistry and Coke Transformation of FCC Coked Catalyst during the Regeneration Process - Shi, Junjun (Sci Rep, 2016)
Regeneration of the coked catalyst is an important process of fluid catalytic cracking (FCC) in petroleum refining, however, this process will emit environmentally harmful gases such as nitrogen and carbon oxides. Transformation of N and C containing compounds in industrial FCC coke under thermal decomposition was investigated via TPD and TPO to examine the evolved gaseous species and TGA, NMR and XPS to analyse the residual coke fraction. Two distinct regions of gas evolution are observed during TPD for the first time, and they arise from decomposition of aliphatic carbons and aromatic carbons. Three types of N species, pyrrolic N, pyridinic N and quaternary N are identified in the FCC coke, the former one is unstable and tends to be decomposed into pyridinic and quaternary N. Mechanisms of NO, CO and CO(2) evolution during TPD are proposed and lattice oxygen is suggested to be an important oxygen resource. Regeneration process indicates that coke-C tends to preferentially oxidise compared with coke-N. Hence, new technology for promoting nitrogen-containing compounds conversion will benefit the in-situ reduction of NO by CO during FCC regeneration.